2022
DOI: 10.3389/fgene.2022.829841
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Biomarkers With Diagnostic Value and Immune Infiltration in Burn Injury

Abstract: Burn injury is an intractable problem in the field of surgery where screening relevant target genes and exploring pathological mechanisms through bioinformatic methods has become a necessity. Herein, we integrated three burn injury mRNA microarray datasets from the Gene Expression Omnibus database to analyze the hub differentially expressed genes (DEGs) between burn injury patient samples and healthy human samples; we conducted multiple functional enrichment analyses and constructed the protein–protein interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The POLQ gene encodes DNA polymerase θ, a 2590 amino acid protein product harboring DNA-dependent ATPase, template-dependent DNA polymerase, dNTP-dependent endonuclease, and 5′-dRP lyase functions (Zahn and Jensen 2021 ). In addition, Sitong Zhou also proved that VASP and POLQ can serve as diagnostic markers in burn processes (Zhou et al 2022 ). Our study also revealed that POLQ was significantly elevated after SARS-CoV2 infection, however, the diagnostic value was not satisfactory in the end.…”
Section: Discussionmentioning
confidence: 99%
“…The POLQ gene encodes DNA polymerase θ, a 2590 amino acid protein product harboring DNA-dependent ATPase, template-dependent DNA polymerase, dNTP-dependent endonuclease, and 5′-dRP lyase functions (Zahn and Jensen 2021 ). In addition, Sitong Zhou also proved that VASP and POLQ can serve as diagnostic markers in burn processes (Zhou et al 2022 ). Our study also revealed that POLQ was significantly elevated after SARS-CoV2 infection, however, the diagnostic value was not satisfactory in the end.…”
Section: Discussionmentioning
confidence: 99%